The effects of the CXCR2 antagonist, MK-7123, on bone marrow functions in healthy subjects - Hastrup, Nina; Khalilieh, Sauzanne; Dale, David C.; Hanson, Lars G.; Magnusson, Peter; Tzontcheva, Anjela; Tseng, Jack; Huyck, Susan; Rosenberg, Elizabeth; Krogsgaard, Kim (Cytokine (Philadelphia, Pa.), 2015)
•CXCR2 antagonists such as MK-7123 may be useful anti-inflammatory agents.•MK-7123 results in a reversible decline in absolute neutrophil counts (ANC).•The mechanism of neutrophil decline is unknown.•The effect of MK-7123 on myelopoiesis was evaluated as a mechanism of ANC decline.•The decrease in ANC was without measurable myelosuppressive effects. The CXCR2 antagonist MK-7123 causes dose-dependent reductions in absolute neutrophil counts (ANC) and decreases neutrophil tissue responses, but its effects on bone marrow functions are not yet known. We conducted a double-blind, randomized study in 18 healthy subjects comparing the effects of either MK-7123 (30mg, po, daily for 28days) or placebo on peripheral blood counts and bone marrow myeloid cell populations. MK-7123 caused a reversible decrease (approximately 50%) in the ANC as demonstrated on days 1 and 28, the first and last days of the treatment period. Bone marrow aspirate smears and biopsy imprints did not differ in the proportion of mature neutrophils in pretreatment, day 28, day 56 or placebo samples. There were no treatment effects on biopsy or aspirate clot cellularity, myeloid to erythroid or myeloid post-mitotic to mitotic ratios; flow-cytometric analyses of aspirate cells; or bone marrow fat to cell balance as assessed by MRI. MK-7123 was generally well tolerated with neutropenia being the most common adverse event; however, there were no clinical symptoms associated with decreased ANCs. These findings indicate that the CXCR2 antagonist MK-7123 causes rapidly reversible decrease in the ANC without measurable myelosuppressive effects. The results support the development of CXCR2 antagonists as potentially useful anti-inflammatory agents, primarily interrupting neutrophil trafficking.